PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA YAYASAN SAYAP IBU CABANG PROVINSI BANTEN - Janah, Miftahul; Maharani, Haidilia (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of workload and work environment on employee job satisfaction at Sayap Ibu Foundation Branch of Banten Province. This research method uses quantitative methods with a descriptive approach. The sampling technique used saturated sampling, namely as many as 58 respondents. The analytical techniques used are validity test, reliability test, classic assumption test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The research results prove that Workload (X1) and Work Environment (X2) have a significant effect, both partially and simultaneously, on Employee Job Satisfaction (Y). The determination obtained by R Square is 0.196, so it can be concluded that the workload variable (X1) influences the employee job satisfaction variable (Y) by 19.6% while the remaining 80.4% is influenced by other factors. The determination obtained by R Square is 0.332, so it can be concluded that the work environment variable (X2) influences the employee job satisfaction variable (Y) by 33.2% while the remaining 66.8% is influenced by other factors. Determination obtained R Square of 0,346, meaning that the variables of workload and work environment together have an influence contribution of 34,6% on employee job satisfaction. While the remaining 65,4% is influenced by other factors not examined in this study.